Em busca de um novo território!! Estudantes dos anos iniciais aprendendo sobre o conceito de localização - Costa, Jonathas Rodrigues Siqueira (2022)
This study consists of an investigation about Geometry conceptual nexuses’ appropriation, related to location geometric concept. The research starts from reflections on the teaching organization, the logical-historical movement of geometric knowledge and the formation of concepts in Vygotsky, in order to understand the complexity of learning and of human development from the cultural-historical aspects. The following question concerns us: What are the signs of location concept’s appropriation by students in the early years in a teaching institution based on the theoretical assumptions of cultural-historical approach? The theoretical foundations of this research result from Cultural-Historical Theory (CHT), Activity Theory (AT) and theoretical-methodological assumptions of Teaching Guiding Activity (TGA) as we consider them a guide of an education process for humanization and for development of concepts formation from the needs that led man to use Geometry in his daily life. To understand this problem, the concept of ‘unit of analysis’ proposed by Vygotsky (2001) is adopted. Due to the Covid-19 pandemic, it was not possible to explore in the field to obtain empirical data. Thus, the data that allow the analysis are result of a didactic-formative experiment carried out in a public school in Goiânia/GO (Brazil) by another researcher of this Postgraduate Program in Education in Mathematics Science (PhD level). The experiment is composed of various triggering learning situations that were objectified in tasks developed in 2018 and 2019, in a municipal school of Goiânia, with children from the 4th grade and, later, from the 5th grade. The oral and written reports of the students who participated in the didactic-training experiment subsidized the investigation of signs of appropriation, by those students, of geometric localization knowledge, based on the theoretical assumptions of Historical-Cultural approach. From the data obtained, we established two units of analysis: the multiple forms of meaning of location and the indications of the development of location concept. This investigation demonstrates the signs of students' transformation from interaction, cooperation, strategies, operations and actions in the search for problem solving, which enables a qualitative change in their actions and in the development of human theoretical thinking. This movement of interaction made possible the appropriation of the concept of location through the improvement of the senses and spatial perception, developing the systematization of knowledge of location, interrelated with the knowledge of sensory, practical and formal geometry.